P40 and P75 Are Singular Functional Muramidases Present in the Lactobacillus casei /paracasei/rhamnosus Taxon - Bäuerl, Christine; Abitayeva, Gulyaim; Sosa-Carrillo, Sebastián; Mencher-Beltrán, Ana; Navarro-Lleó, Noemí; Coll-Marqués, José M.; Zúñiga-Cabrera, Manuel; Shaikhin, Serik; Pérez-Martinez, Gaspar (Frontiers in Microbiology, 2019)
Lactobacillus casei and Lactobacillus rhamnosus proteins P40 and P75 belong to a large family of secreted cell wall proteins that contain a carboxy(C)-terminal CHAP or NlpC/P60 superfamily domains. In addition to their peptidoglycan hydrolase activity, proteins in this family are specific antigens of pathogens, frequently responsible of interactions with the host. , L. rhamnosus GG and L. casei BL23 purified P40 and P75 proteins have antiapoptotic activity by inducing the EGF/Akt pathway. The aim of this work was to study the genetics, phylogeny and dissemination of this family of proteins in the genus Lactobacillus as well as their characteristics and likely function. The scrutiny of their DNA encoding sequences revealed the presence of minisatellite DNA in the P75 encoding gene of L. casei/paracasei strains (cmuB) with intraspecific indels that gave raise to four different alleles (cmuB1-4), which are exclusive of this species. Phylogenic analyses suggest that both proteins are present mainly in the L. casei and Lactobacillus sakei phylogenomic groups. A P40 ancestral gene was possibly present in the common ancestor of Enterococcaceae, Lactobacillaceae and Streptococcaceae. P75 is also present in L. casei and L. sakei groups, but its evolution is difficult to explain only by vertical transmission. Antibodies raised against the N-terminal regions of P40 and P75 improved their immunological detection in culture supernatants as they recognized almost exclusively proteins of L. casei/ paracasei/ rhamnosus strains, highlighting their structural similarity, that and allowed to detect them in some different fermented dairy products that contained probiotic L. casei strains. Purified P40 and P75 proteins showed no evident lytic activity but they complemented L. casei BL23 cmuA and cmuB defective mutants, respectively, thus proving that they actively participate in cell division.